The Rohingya Crisis: Dehumanization and Denial of Hospitality in First They Erased Our Name: A Rohingya Speaks - Rai, Kamal (Pashupati Pragya पशुपति प्रज्ञा, 2025)
This article explores the Rohingya refugee crisis by analyzing Habibhuraman’s "First They Erased Our Name: A Rohingya Speaks." It focuses on the Rohingya immigrants’ horrendous lives after being stateless as an outcome of the ethnic conflicts in Myanmar since the decades of the 1980s. The prime concern is, why Rohingya people turn into the stage of dehumanization and how they wander across the world facing a lack of cordial hospitality. The study significantly unveils the government’s severe acts of dehumanization by suspending the fundamental rights of the Rohingya minority. Thus, they are forced to begin a never-ending, precarious journey, abandoning their inherited land, Arakan Myanmar, and their overall identity. Instead of warm friendliness, the Rohingya are destined to face a stark denial of unconditional hospitality wherever they happen to visit across the world. This paper methodologically embraces the theoretical framework of Hanna Arendt and Giorgio Agamben to illustrate the plight of the Rohingya as a refugee crisis. In contrast, the ideas of Jacques Derrida and Emmanuel Levinas are employed to address the Rohingya refugee crisis as the solution. In this article, therefore, the researcher mainly emphasises the protagonist of the novel Habib to mirror the realistic misery of the Rohingya whose unsafe travel to more than dozens of countries as a non-citizen is an accurate depiction of the entire community. In his journey, the hardship from his ancestral to the visited countries is due to his stateless position. The Rohingya, hence, are in torture, humiliation, despair, and suffering since they are excluded from the political sphere.